Therapeutic use of the humanoid robot, Telenoid, with older adults: A critical interpretive synthesis review - Moyle, Wendy; Murfield, Jenny; Lion, Katarzyna (Assistive technology, 2024)
This review sought to critically evaluate the use of the teleoperated humanoid robotic communications device, Telenoid, for therapeutic purposes with older adults, and identify and highlight key considerations for future research and clinical practice within gerontechnology. A critical interpretive synthesis was conducted, with nine electronic databases and online sources searched using the keyword "Telenoid." Studies were included in the review if they were: written in English; reported primary research; employed a qualitative, quantitative, or mixed-method design; and described or measured effects, experiences, or perceptions of using Telenoid for therapeutic purposes with older adults. Critical engagement with the studies identified key themes, as well as opportunities to advance future research. Ten studies involving Telenoid were identified, with eight focused on older adults living with dementia. Study findings centered around two themes: effects (including positive effects and negative reactions), and challenges and considerations (including technical issues, operator training, acceptability, and dosage). Although several issues currently challenge the use of Telenoid, available studies show some therapeutic potential of using Telenoid with older adults, including those living with dementia, particularly for communication and mood. Higher-quality studies are required to advance understanding, and considerations for the field are outlined to aid development.